Cryogenic 3D Printing of GelMA/Graphene Bioinks: Improved Mechanical Strength and Structural Properties for Tissue Engineering - Santana MDV; Magulas MBS; Brito GC; Santos MC; de Oliveira TG; de Melo WGG; Argolo Neto NM; Marciano FR; Viana BC; Lobo AO (International Journal of Nanomedicine, 2024)
Moises das Virgens Santana,1 Maria Beatriz S Magulas,1 Guilherme Castro Brito,1 Mariana Chaves Santos,1 Tainara Gomes de Oliveira,1 Wanderson Gabriel Gomes de Melo,2 Napoleao Martins Argolo Neto,2 Fernanda Roberta Marciano,1,3 Bartolomeu Cruz Viana,1,3 Anderson Oliveira Lobo1 1LIMAV-Interdisciplinary Laboratory for Advanced Materials, UFPI - Federal University of Piaui, Teresina, PI, 64049-550, Brazil; 2Integrated Center for Morphology and Stem Cell Research, Postgraduate Program in Technologies Applied to Animals of Regional Interest, Federal University of Piaui, Teresina, PI, 64049-550, Brazil; 3Department of Physics, UFPI - Federal University of Piaui, Teresina, PI, 64049-550, BrazilCorrespondence: Anderson Oliveira Lobo, Email lobo@ufpi.edu.brPurpose: Tissue engineering aims to recreate natural cellular environments to facilitate tissue regeneration. Gelatin methacrylate (GelMA) is widely utilized for its biocompatibility, ability to support cell adhesion and proliferation, and adjustable mechanical characteristics. This study developed a GelMA and graphene bioink platform at concentrations of 1, 1.5, and 2 mg/mL to enhance scaffold properties for tissue engineering applications.Patients and Methods: Graphene was incorporated into GelMA matrices to improve mechanical strength and electrical conductivity of the bioinks. The compressive strength and thermal stability of the resulting GelMA/graphene scaffolds were assessed through DSC analysis and mechanical testing. Cytotoxicity assays were conducted to determine cell survival rates. Cryoprinting at − 30°C was employed to preserve scaffold structure and function. The chorioallantoic membrane (CAM) assay was used to evaluate biocompatibility and angiogenic potential.Results: The integration of graphene significantly amplified the compressive strength and thermal stability of GelMA scaffolds. Cytotoxicity assays indicated robust cell survival rates of 90%, confirming the biocompatibility of the developed materials. Cryoprinting effectively preserved scaffold integrity and functionality. The CAM assay validated the biocompatibility and angiogenic potential, demonstrating substantial vascularization upon scaffold implantation onto chick embryo CAM.Conclusion: Integrating graphene into GelMA hydrogels, coupled with low-temperature 3D printing, represents a potent strategy for enhancing scaffold fabrication. The resultant GelMA/graphene scaffolds exhibit superior mechanical properties, biocompatibility, and pro-vascularization capabilities, making them highly suitable for diverse tissue engineering and regenerative medicine applications.Keywords: GelMA, graphene, cryoprinting, hydrogels and tissue engineering